Fracture behavior of thermally aged Ag–Cu composite sinter joint through microscale tensile test coupled with nano X-ray computed tomography. (August 2021) - Matsuda, Tomoki; Yamada, Seigo; Takeuchi, Akihisa; Uesugi, Kentaro; Yasutake, Masahiro; Sano, Tomokazu; Ohata, Mitsuru; Hirose, Akio
Graphical abstract: Highlights: Aging induced Cu oxidation with good bondability to sintered Ag and Cu substrate. Microtensile test enabled the observation of Ag deformation and crack initiation. Fracture occurred between sintered Ag and Cu oxide flake after maximum stress. Composite sinter layer contributes to the fracture and the mechanical properties. Coupled nano-CT supports the understanding of intrinsic fracture behavior. Abstract: Herein, we investigated the fracture behavior of thermally aged Ag–Cu composite sinter joints through nano-X-ray computed tomography (nano-CT) combined with microscale tensile testing. Nano-CT results showed that the joint comprised Ag/oxidized Cu flake sintered layer and Cu oxide, which was formed on the Cu substrate; further, pores were present at the interface between the substrate and Cu oxide layer. The tensile test showed that the stress increased with plastic deformation up to a maximum of 308 MPa, before a subsequent steep decrease due to crack initiation inside the sintered layer. The nano-CT and in situ observation results suggest that the microscale joint fractured through the interface between the oxidized Cu flake and Ag. Results obtained herein suggest that microscale tensile testing coupled with nano-CT is an effective approach to describe the intrinsic fracture behavior of joints.